Responsibility and Redistribution: The Case of First Best Taxation - Bertil Tungodden (Center for Economic Studies and ifo Institute (CESifo), 2001)
It is not straightforward to define the ethics of responsibility in cases where the consequences of changes in factors within our control are partly determined by factors beyond our control. In this paper, we suggest that one plausible view is to keep us responsible for the parts of the consequences that are independent of the factors beyond our control. Within the framework of a first best taxation problem, we present and characterise a redistributive mechanism that both satisfies this interpretation of the ethics of responsibility and the ethics of compensation within a broad class of economic environments. However, on a general basis, even this weaker version of the ethics of responsibility is not compatible with the ethics of compensation, and we report an impossibility result that clarifies the source of this conflict.
Keywords: 330; redistribution; responsibility; compensation